Toxicity of Irradiated Medium for Repair-Deficient Strains of Escherichia coli - Webb, Robert B. (1972)
Nutrient agar medium is made highly toxic to certain repair-deficient strains of Escherichia coli by exposure of the uninoculated plates to radiation from cool-white fluorescent lamps or black-light fluorescent lamps. This sensitivity is associated with the genetic deficiencies, fil, phr, and recA. Repair-sufficient and uvr strains are only slightly affected by the irradiated media. The poor growth and reduced plating efficiency frequently associated with BPhr and recA strains are very likely caused by inadvertent exposure of the medium to fluorescent light.